Analysis of Institutional Efficiency and Donor Utility: A Study of Integrated Service Quality in the Philanthropy Sector - Azizan Sentosah Hutabarat; Alvien Septian Haerisma; Anton Sudrajat (JURNAL ECONOMINA, 2026)
The transformation of philanthropy management demands institutional professionalism in providing excellent service to the public. This study aims to explore institutional efficiency and the utility of donors through the quality of integrated services at BAZNAS Majalengka. Data collection involved active donors as providers of experiential insights, management staff to examine operational procedures, and digital documents as evidence of accountability. Through a qualitative case study, the data was analyzed to map subjective satisfaction and service transparency. The results indicate that service integration effectively minimizes information asymmetry and transaction costs. These findings confirm that institutional credibility is a key determinant in strengthening the Islamic economic ecosystem.